Local Existence for the Generalized Navier-Stokes-Maxwell Equations (Journal of Nonlinear Modeling and Analysis, 2025)
In this paper, we establish the local existence for the generalizedNavier-Stokes-Maxwell system with the fractional velocity dissipative term $Λ^{2α}u$ and fractional magnetic dissipative term $Λ^{2β}B.$ Moreover, we establishthe global existence of strong solutions to this generalized model.
Keywords: Navier-Stokes-Maxwell system; fractional dissipative; local existence; global existence.